2008
DOI: 10.1016/j.jvs.2007.09.062
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular stenting versus open surgery for thoracic aortic disease: Systematic review and meta-analysis of perioperative results

Abstract: Endovascular thoracic aortic repair reduces perioperative mortality and neurological morbidity in patients with descending thoracic aortic aneurysms. There may be less benefit in other thoracic aortic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(123 citation statements)
references
References 38 publications
1
108
0
9
Order By: Relevance
“…The evidence for efficacy and safety has been mainly derived from large multicenter registries (9,10). Single center retrospective studies evaluating individual diseases within ATAS, have revealed better outcome compared with open surgery with regard to complicated type-B AD, aortic transection, and ruptured descending thoracic aneurysm (11)(12)(13)(14). The debate on timing of aortic intervention is currently ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for efficacy and safety has been mainly derived from large multicenter registries (9,10). Single center retrospective studies evaluating individual diseases within ATAS, have revealed better outcome compared with open surgery with regard to complicated type-B AD, aortic transection, and ruptured descending thoracic aneurysm (11)(12)(13)(14). The debate on timing of aortic intervention is currently ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Desse modo, a perda sanguínea é bem menor do que a produzida com a cirurgia convencional, a aorta não precisa ser pinçada e a recuperação do paciente é mais rápida. Vários estudos prospectivos e randomizados estão sendo conduzidos no sentido de comparar a técnica convencional com a endovascular [5][6][7][8][9][10] 14 . Já no Brasil, apesar de não haverem muitos estudos multicêntricos comparativos, houve melhora significativa da morbidade e de complicações pós-operatórias no trauma torácico desde a adoção do tratamento endovascular 15,16 .…”
Section: Discussionunclassified
“…In the past, TEVAR was positioned as the main treatment strategy for TAA or traumatic aortic transection after its clinical introduction in 1994 [16]. Various studies demonstrated that the minimally invasive procedure of TEVAR might allow rapid control of blood loss even in patients with hemodynamic instability [17,18], and that the perioperative morbidity of TEVAR during an urgent condition was significantly better than that of emergency open surgery [19]. After the usefulness of TEVAR in closing a fistula between the aorta and an adjacent organ was reported in 1996 [20], numerous promising results in its short-term effectiveness have encouraged its clinical use, and the indications of TEVAR have expanded to AEF.…”
Section: Etiologies Of Aorto-esophageal Fistulamentioning
confidence: 99%